(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
To guarantee access to education, institutions must accept students with special educational needs (SEN) and within this are students with ADHD, these being the subjects that will be addressed in the re-search, likewise I choose to teach them a fundamental topic such as the probability, but taking into ac-count the subjective probability as a central axis allowing to see the knowledge and perceptions acquired of the probability in their environment. Following this, a series of activities were designed using board games such as dominoes, chess, ludo, among others; During the process, a logbook was kept recording the probabilistic thinking that previously existed in them, but the probability in each of the games was not explained in the same way, in some cases it was explained from personal experiences to specific num-bers by means of estimates, all of them These findings allow us to observe that in the game the students achieve subjective probabilistic thinking.